Beginning Mac OS X Snow Leopard programming - Trent, Michael, 1972- (Wrox beginning guides., 2010)
A solid introduction to programming on the Mac OS X Snow Leopard platformThe Mac OS X Snow Leopard system comes with everything you need in its complete set of development tools and resources. However, finding where to begin can be challenging. This book serves as an ideal starting point for programming on the Mac OS X Snow Leopard platform. Step-by-step instructions walk you through the details of each featured example so that you can type them out, run them, and even figure out how to debug them when they don't work right. Taking into account that there is usually more than one way to do something when programming, the authors encourage you to experiment with a variety of solutions. This approach enables you to efficiently start writing programs in Mac OS X Snow Leopard using myriad languages and put those languages together in order to create seamless applications.